2008
DOI: 10.1016/j.ultramic.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy study of the antibacterial effects of chitosans on Escherichia coli and Staphylococcus aureus

Abstract: Chitosan has been reported to be a non-toxic, biodegradable antibacterial agent. The aim of this work was to elucidate the relationship between the molecular weight of chitosan and its antimicrobial activity upon two model microorganisms, one Gram-positive (Staphylococcus aureus) and one Gram-negative (Escherichia coli). Atomic force microscopy (AFM) imaging was used to obtain high-resolution images of the effect of chitosans on the bacterial morphology. The AFM measurements were correlated with viable cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
168
3
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(205 citation statements)
references
References 41 publications
21
168
3
5
Order By: Relevance
“…This supports the evidence that the leakage of intracellular material observed by chitosan in gram-negative is superior to that reported in gram-positive bacteria [21][22][23] . [28][29][30][31] .…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…This supports the evidence that the leakage of intracellular material observed by chitosan in gram-negative is superior to that reported in gram-positive bacteria [21][22][23] . [28][29][30][31] .…”
Section: Introductionsupporting
confidence: 89%
“…These findings are confirmed by several in vitro experiments in which gram-negative bacteria appear to be very sensitive to chitosan, exhibiting increased morphological changes on treatment when compared to gram-positives [22,23,[33][34][35] . The charge density on the cell surface is a determinant factor to establish the amount of adsorbed chitosan.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Fosfomycin has the ability to penetrate into the fluid of the interstitial space of soft tissues (Frossard et al 2000) to reach levels sufficient to substantially inhibit the growth of relevant bacteria at the target site. The pharmacokinetic and pharmacodynamic properties of fosfomycin facilitate design of drug doses with clinically relevant concentrations for sites such as lungs, bone, soft tissue, and serum and heart valves (Roussos et al 2009 (Eaton et al 2008), kyotorphin peptide (Ribeiro et al 2012), carvacrol (Storia et al 2011) on Staphylococcal aureus biofilms. The nanoscale visualization and characterization of Staphylococcus aureus cells (Ribeiro et al 2012) demonstrated that kyotorphin perturbed the bacterial cell-wall membrane by blebbing, lysis and disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Bactericidal activity of the gluten peptide-chitosan conjugates was observed when both types of chitosan were used, but the presence of HMWC in a conjugate made this more active, especially at low temperatures. Atomic force spectroscopy was also used to investigate the molecular weight dependency of the antibacterial effect of chitosans, but this time against Escherichia coli and Staphylococcus aureus (Eaton et al, 2008). These studies also allowed the response strategies used by Gram-negative and Gram-positive bacteria to be compared.…”
Section: Antimicrobial Activitymentioning
confidence: 99%